High‐resolution functional MRI at 3 T: 3D/2D echo‐planar imaging with optimized physiological noise correction. Issue 6 (20th July 2012) - Lutti, Antoine; Thomas, David L.; Hutton, Chloe; Weiskopf, Nikolaus
Abstract: High‐resolution functional MRI (fMRI) offers unique possibilities for studying human functional neuroanatomy. Although high‐resolution fMRI has proven its potential at 7 T, most fMRI studies are still performed at rather low spatial resolution at 3 T. We optimized and compared single‐shot two‐dimensional echo‐planar imaging (EPI) and multishot three‐dimensional EPI high‐resolution fMRI protocols. We extended image‐based physiological noise correction from two‐dimensional EPI to multishot three‐dimensional EPI. The functional sensitivity of both acquisition schemes was assessed in a visual fMRI experiment. The physiological noise correction increased the sensitivity significantly, can be easily applied, and requires simple recordings of pulse and respiration only. The combination of three‐dimensional EPI with physiological noise correction provides exceptional sensitivity for 1.5 mm high‐resolution fMRI at 3 T, increasing the temporal signal‐to‐noise ratio by more than 25% compared to two‐dimensional EPI. Magn Reson Med, 2013. © 2012 The Authors. Magnetic Resonance in Medicine Published by Wiley Periodicals, Inc. on behalf of International Society of Medicine in Resonance.